MEASURING THE PERFORMANCE OF ISLAMIC BANKS THROUGH RISK PROFILE, EARNING, AND CAPITAL - Bambang Iswanto; Angrum Pratiwi; Idhafiyyah Anwar (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The emergence of COVID-19 as a global pandemic has impacted slowing economic growth, which has also affected regional financial and banking stability in East Kalimantan. This study aims to describe the results of measuring the performance of Islamic Commercial Banks using the risk profile, earning & capital method. The research population is Islamic banks operating in the Samarinda area of ​​East Kalimantan, and the research sample selection is purposive sampling. The study results show that the measurement in terms of the risk profile aspect shows an average rating of 2,